Assertive communication in teachers: diagnosis and educational proposal - Cañas, Dora Cristina; Hernández, Jacqueline (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Assertive communication has been included as one of the social skills or life skills that are key to the promotion of human development and the prevention of psychosocial problems. The aim of this study was to make a diagnosis of it from its personal dimension versus sociodemographic characteristics in teachers, and from the findings an educational intervention design was made. The applied method was quantitative through a descriptive transectional study, which 39 teachers of both sexes. The results indicate that most of the participants are located in the average range up, which accounts for being assertive when communicating. However, statistically significant differences were found for Factor 3, with respect to the level of training (F = 4.189, p = 0.048) and years of experience (F = 3.39, p = 0.045); as well as in Factor 5 with respect to the number of children (F = 5.14, p = 0.029). Also, it is concluded that it is necessary to reinforce and improve some characteristics of this communication, for which an educational program was proposed.